RehabilitationAttempt to assess the physical fitness of elderly patients eligible for resection of lung parenchyma using the Fullerton test - Bal-Bocheńska, Monika; Kądziołka, Wojciech; Kądziołka, Joanna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Aim: To evaluate physical fitness with the Fullerton test in patients referred for thoracic procedures. Material and methods: The study included 35 patients aged 60-70 years (mean 66.8 years): 17 women and 18 men. Physical fitness was assessed using a test for the elderly (Fullerton Rikli & Jones). Results: The Fullerton test was well tolerated by thoracic surgery patients. During the study, and immediately afterwards, there was no shortness of breath, fainting, loss of saturation or deterioration of well-being of patients. Most patients showed an improvement in spirometric values ​​(vital capacity – VC% to 20%, forced expiratory volume in one second % of vital capacity – FEV1%VC of 22%). There was a positive hemodynamic response in systolic blood pressure (50-80%) and heart rate (77-90%) rated the most serious attempts to determine aerobic endurance and strength endurance of the upper and lower body. Conclusions : The Fullerton test can be safely used in patients referred for thoracic procedures. As a new, reproducible method of testing, it can complement the comprehensive diagnosis of patients undergoing surgery.